From collaborative to institutional reflexivity: Calibrating responsibility in the funding process. (15th October 2020) - Grimpe, Barbara; Stahl, Bernd Carsten; Ten Holter, Carolyn; Inglesant, Philip; Eden, Grace; Patel, Menisha; Jirotka, Marina
Abstract: Science–policy organisations are expected to be reflexive of their political influence on research and society. In this long-standing discourse on institutional reflexivity, formal organisations have largely been considered as a whole, and from a structural, or systemic perspective, whereas much less is known about everyday organisational practices; how individual organisational members reflect on and act upon their own as well as their organisation's limits of knowledge and pre-commitments, if at all. We address this gap through an analysis of qualitative interviews with one national funding institution's staff overseeing funding for research into information and communication technologies. We develop a bridging concept between individual and institutional reflexivity, which we call 'collaborative reflexivity'. Through collaborative reflexive processes, individual employees contribute to the entire organisation's institutional reflexivity. Our findings help to better understand 'responsible' behaviour in funding processes, as part of the growing international movement of Responsible Research and Innovation.